Electrostatic-interaction-driven assembly of binary hybrids towards fire-safe epoxy resin nanocomposites - Liu, Lu (2019)
Manganese dioxide (MnO2), as a promising green material, has recently attracted considerable attention of researchers from various fields. In this work, a facile method was introduced to prepare binary hybrids by fabricating three-dimensional (3D) zinc hydroxystannate (ZHS) cubes on two-dimensional (2D) MnO2 nanosheets towards excellent flame retardancy and toxic effluent elimination of epoxy (EP) resin. Microstructural analysis confirmed that the morphologies and structures of MnO2@ZHS binary hybrids were well characterized, implying the successful synthesis. Additionally, the morphological characterization indicated that MnO2@ZHS binary hybrids could achieve satisfactory interfacial interaction with the EP matrix and be well dispersed in nanocomposites. Cone calorimeter test suggested that MnO2@ZHS binary hybrids effectively suppressed the peak of heat release rate and total heat release of EP nanocomposites, performing better than MnO2 or ZHS alone. Condensed-phase analysis revealed that MnO2@ZHS binary hybrids could promote the char density and graphitization degree of char residues and thereby successfully retard the permeation of oxygen and flammable gases. Moreover, through the analysis of gas phase, it can be concluded that MnO2@ZHS binary hybrids could efficiently suppress the production of toxic gases during the degradation of EP nanocomposites. This work implies that the construction of 2D/3D binary hybrids with an interfacial interaction is an effective way to fabricate high-performance flame retardants for EP.